A Content Analysis of the WH-Questions in the EFL Textbook of That's Right - Igbaria, Abdul Kareem; Ghanayem , Asmaa (Advances in Social Sciences Research Journal, 2020)
In the current study, the researchers analyzed the units of the textbook “That’s Right” for 10th grade students for English teaching in Israel. The study examined the WH- questions found in the textbook according to the various cognitive levels of Bloom’s Taxonomy. By using Bloom's taxonomy, the researchers attempted to understand whether WH-questions used in the textbook emphasize high-level thinking and cognitive skills development. The question of this study is: To what extent do the WH-questions in the textbook “That’s Right” emphasize higher order thinking skills? Content analysis was performed for the questions for five study units in the textbook. The question served as the unit of analysis for this research. A WH-question is defined as a question beginning with a WH-word and ending with a question mark. The questions were collected, listed, and analyzed according to Bloom's taxonomy, according to which thinking skills are divided into low and high orders. Low order thinking skills are knowledge, comprehension, and application. High order thinking skills are: analysis, synthesis, and evaluation. Percentages and frequencies of each cognition level were calculated for each book unit separately and for all the units combined. Validation and reliability checks were performed to validate this study. The results showed that 245 out of the 324 questions emphasized cognition levels that develop lower order thinking skills, while only 79 questions emphasized the three levels that use high order thinking skills. The textbook "That’s Right" questions place most emphasis on comprehension and knowledge, which are both connected to lower order thinking skills. This may result in lower cognitive abilities among students and should be further investigated to create better language skills in future generations. Additional studies of English textbooks at various age levels using content analysis are recommended. These studies will show which cognitive skills are developed in English materials and will improve future English education in Israel.